Assessing gross motor skills development among children with visual impairment - Nagoor Meera Abdullah; Vincent Parnabas; Mohd Soffian Omar-Fauzee; Mohd Nizam Nazarudin (Contemporary Research Center CRC Publications, 2014)
The purpose of this study was to assess the gross motor skills development among visually impaired children Total of 15 visually-impaired children participated in this study (7 males and 8 females), divided into three disability groups that are B1,B2 and B3 with age range between 7 -10 years old. They were assessed on locomotor and object control skills that include running, galloping, hoping, leaping, horizontal jumping, and sliding, striking, dribbling, kicking, catching, throwing and underhand roll. The subjects perform the Test of Gross Motor Development-2. One Sample T-Test was used to analyze the significant of the hypothesize showed that there was significant lower object control but not locomotor skill scores. (t=19.007, p=.000<0.05). The mean value for Locomotor Skills for running group B1 is 6.60±.894, group B2 is 7.00±1.732 and group B3 is 7.20±1.095 while for gallop group B1 is 4. 6.00±2.828.The gross motor skill result of the subjects are at the satisfactory level and the subjects give a full cooperation.